2018
DOI: 10.1159/000491634
|View full text |Cite
|
Sign up to set email alerts
|

Parietal Involvement in Constructional Apraxia as Measured Using the Pentagon Copying Task

Abstract: Deficits in copying (“constructional apraxia”) is generally defined as a multifaceted deficit. The exact neural correlates of the different types of copying errors are unknown. To assess whether the different categories of errors on the pentagon drawing relate to different neural correlates, we examined the pentagon drawings of the MMSE in persons with subjective cognitive complaints, mild cognitive impairment, or early dementia due to Alzheimer’s disease. We adopted a qualitative scoring method for the pentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…Deficits in the well-known Pentagon Copying Task were related to GM volumes of the total parietal (for total score) and specific sub-regions of the parietal cortex (such as the posterior cingulate cortex and supramarginal gyrus, for intersection and the number of angle scores) in AD, MCI and SCD cases, conceptualizing the constructional apraxia as a failure in the integration of visual information from one fixation point to the next. 80 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficits in the well-known Pentagon Copying Task were related to GM volumes of the total parietal (for total score) and specific sub-regions of the parietal cortex (such as the posterior cingulate cortex and supramarginal gyrus, for intersection and the number of angle scores) in AD, MCI and SCD cases, conceptualizing the constructional apraxia as a failure in the integration of visual information from one fixation point to the next. 80 …”
Section: Resultsmentioning
confidence: 99%
“…Deficits in the well-known Pentagon Copying Task were related to GM volumes of the total parietal (for total score) and specific sub-regions of the parietal cortex (such as the posterior cingulate cortex and supramarginal gyrus, for intersection and the number of angle scores) in AD, MCI and SCD cases, conceptualizing the constructional apraxia as a failure in the integration of visual information from one fixation point to the next. 80 Different studies are also targeting executive and frontal-lobe functioning in MCI, AD and healthy controls. [81][82][83] Authors of a multimodal MRI study in healthy adults showed that low deactivation of the DMN, high activation of the executive-control network and high WMH burden were the most accurate predictors of executive functioning at baseline.…”
Section: Mri and Cognitionmentioning
confidence: 99%
“…Copying tasks require several complex cognitive functions, including visuospatial and executive functions. 21 The parietal lobe may be involved in copying tasks since it is bilaterally activated during drawing tasks; 22 moreover, patients with a parietal lobe stroke often present with constructional apraxia. 23 Additionally, a recent study reported a negative correlation between parietal gray matter volumes and qualitative scoring on the pentagon copy test.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Additionally, a recent study reported a negative correlation between parietal gray matter volumes and qualitative scoring on the pentagon copy test. 21 Visual information travels through two pathways: the “what pathway” in the ventral route for perceiving objects and the “where pathway” in the dorsal route for recognizing object positions. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation